2021
DOI: 10.1007/s12403-020-00381-6
|View full text |Cite
|
Sign up to set email alerts
|

Low-Level Environmental Heavy Metals are Associated with Obesity Among Postmenopausal Women in a Southern State

Abstract: Both arsenic and cadmium are reported to be toxic to humans. The use of saliva as a biomarker of low-level exposures to these elements has not been adequately explored, and the putative relationship between exposure and obesity is unclear. This cross-sectional study aims to investigate the relationship between salivary arsenic and cadmium concentrations and their association with obesity. Arsenic and cadmium concentrations were analyzed in human saliva samples by Inductively Coupled Plasma-Mass Spectrometry on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Despite consideration of As as a potential obesogen [43], existing epidemiological data are insufficient and contradictory. A recent study demonstrated that salivary As levels are directly associated with BMI in women [44]. In contrast, urinary As concentration was characterized by inverse association with BMI in Taiwanese subjects [45].…”
Section: Discussionmentioning
confidence: 98%
“…Despite consideration of As as a potential obesogen [43], existing epidemiological data are insufficient and contradictory. A recent study demonstrated that salivary As levels are directly associated with BMI in women [44]. In contrast, urinary As concentration was characterized by inverse association with BMI in Taiwanese subjects [45].…”
Section: Discussionmentioning
confidence: 98%
“…Physiological criteria, including body and thymus weight, were determined following the methods described by Farhangi et al ( 2017 ) and Kong et al ( 2018 ). The weight gain velocity (Sié et al, 2021 ; Stahr et al, 2021 ) was calculated with the formula below: when: N > 2, M = N ‐2; N = 1, M = 0, …”
Section: Methodsmentioning
confidence: 99%
“…Physiological criteria, including body and thymus weight, were determined following the methods described by Farhangi et al (2017) and Kong et al (2018). The weight gain velocity (Sié et al, 2021; Stahr et al, 2021) was calculated with the formula below: when: N > 2, M = N ‐2; N = 1, M = 0,weight0.5emgain0.5emvelocitygoodbreak=weight0.5emat0.5emN0.5emweeksweight0.5emat0.5emM0.5emweeksweight0.5emat0.5emM0.5emweeksgoodbreak×100%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, numerous studies have revealed a significant association between metal­(loid)­s, such as lead, cadmium, and mercury, and obesity as defined by abnormal BMI. However, research on the association between exposure to metal­(loid)­s and WC or AOB defined by abnormal WC is limited. BMI is a common indicator of obesity, reflecting overall body fat, while WC provides insight into the status of visceral fat and abdominal adipose tissue .…”
Section: Introductionmentioning
confidence: 99%